2004
DOI: 10.1016/j.soilbio.2004.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the nitrogen assimilated by soil fauna living in decomposing beech litter

Abstract: We investigated the nitrogen source for main taxa of soil fauna in two beech forests of contrasted humus type using 15 N-labelled beech litter and 15 N analysis of soil fauna. 15 Nlabelled beech litter was deposited on the topsoil in December 2000 in four stands of different ages at Leinefelde (Germany) with mull humus and in one mature stand at Sorø (Denmark) with moder humus. The fate of the tracer isotope was measured in litter and soil, as well as in the soil fauna, and for each taxa, we calculated the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 58 publications
1
19
0
1
Order By: Relevance
“…6/ AV = aveia; AV+N = aveia + adubação nitrogenada; CE = centeio; CE+N = centeio + adubação nitrogenada; DES = solo descoberto. L. C. Gatiboni et al Caner et al, 2004). Ainda, o efeito detectado pode ser devido à menor quantidade de palhada remanescente sobre o solo nos tratamentos sem adubação nitrogenada, principalmente na cultura da aveia preta.…”
Section: Resultsunclassified
“…6/ AV = aveia; AV+N = aveia + adubação nitrogenada; CE = centeio; CE+N = centeio + adubação nitrogenada; DES = solo descoberto. L. C. Gatiboni et al Caner et al, 2004). Ainda, o efeito detectado pode ser devido à menor quantidade de palhada remanescente sobre o solo nos tratamentos sem adubação nitrogenada, principalmente na cultura da aveia preta.…”
Section: Resultsunclassified
“…Researchers found that oribatid mites are one of the most abundant soil meso-fauna in terrestrial ecosystems [54] and can increase microbial activity [55]. However, some fungivorous fauna in turn feed on fungi [56] because they cannot directly utilize resistant litter as a nutrient source [7]. On the other hand, studies have demonstrated that some oribatid mites can stimulate the release of dissolved carbon and nitrogen from fresh litter [55].…”
Section: Discussionmentioning
confidence: 99%
“…Versini et al also demonstrated that the low DOC and TDN concentrations derived from fresh litter can percolate deep into mineral soil [6]. These findings imply that dissolved carbon and nitrogen are important sources of carbon and nutrients for soil decomposers and may be quickly assimilated by soil organisms living on the litter surface [4,7] because of the low molecular weight of the litter leachates [8]. However, information regarding how soil fauna contribute to the release of dissolved carbon and nitrogen from plant litter is limited.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These labile C inputs are necessary to support the extraction of nutrients by mycorrhizal fungi from soil organic matter of low C quality. For example, fungi are quite important in moving N into decomposing litter from lower soil horizons (Frey et al 2003;Caner et al 2004).…”
Section: Fungal Biomassmentioning
confidence: 99%